Development of cognitive diagnostic assessment instruments and a cognitive differentiation student worksheet to measure and improve scientific literacy capability - Joko Supriono; Pramudiyanti; Fatkhur Rohman; ⁠Undang Rosidin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research develops cognitive diagnostic assessment instruments and cognitively differentiated worksheets designed to enhance students' scientific literacy in science learning. Using a Research and Development (R&D) approach based on the Plomp model, the study involved 28 students, each from Class IV A and IV B at MIN 1 North Lampung. Data was collected through documentation, questionnaires, interviews, and observation, and analyzed using t-tests, practicality tests, and product validation. Expert validation showed the instruments and worksheets were highly valid, with average scores of 92% for cognitive diagnostic assessment questions, 94% for post-test questions, and 94% for material, linguistic, and media validation. The practicality test showed educators' responses at 84% and students' at 87%, both rated as very practical. A t-test revealed a significant difference (p = 0.001, p < 0.05) between the experimental and control classes in post-test scores. The results indicate that the developed cognitive diagnostic assessment instruments and differentiated worksheets are valid, practical, and effective in enhancing students' scientific literacy.